Investment influence on east java economic growth - Ignatia Martha H; Sishadiyati Sishadiyati; Muhammad Wahed (Faculty of Economics and Business Mulawarman University, 2022)
This study aims to examine and analyze the effect of investment in the manufacturing industry sector on the economic growth of East Java, Indonesia. The research period is five years, starting from 2004 / 2018. This paper uses the method of multiple linear regression analysis with the findings that explain that foreign investment (PMA) has a positive and significant effect on economic growth. This finding is in line with the reality on the ground that the number of foreign investors who invested in East Java is quite large and the sector that is mostly interested is the food industry sector (culinary). While domestic investment (PMDN) has no significant effect on growth. This condition was influenced by several factors including: 1) Risk Country; 2) low coordination between institutions and; 3) low financial sector connectivity. While efforts to increase investment, can be done through programs of reform, deregulation, and bureaucratization in all aspects of economic development.